Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Stres Guru Bimbingan Konseling yang Dimediasi oleh Gaya Kepemimpinan Kepala Sekolah - Alfi Rahmaniah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was carried out with the following aims, among others, to determine the influence between workload and stress for guidance counselors; to assess the effect of workload on the principal's leadership style; To determine the influence between the work environment and stress for guidance and counseling teachers; To determine the influence of the work environment on the leadership style of school principals; To assess the influence of the principal's leadership style on guidance and counseling teacher stress. This research is quantitative research with a purposive sample of 84 guidance and counseling teachers in the East Jakarta research area. The research results found that the path coefficient value of workload on work stress was 0.166 with P-Values ​​of 0.195 > 0.05 and stat of 1.296 <1.96. Thus, workload does not affect work stress, the path coefficient value of workload on leadership style is 0.049 with P-Values ​​of 0.672 > 0.05 and tstat 0.424 <1.96. Thus, H2 workload does not affect leadership style, the path coefficient value of the work environment on work stress is 0.343 with P-Values ​​of 0.047<0.05 and tstat 1.987>1.96. Thus the work environment influences work stress, the path coefficient value of the work environment on leadership style is 0.438 with P-Values ​​of 0.000<0.05 and tstat 1.601>1.96. Thus, the work environment influences leadership style, the path coefficient value of leadership style on work stress is 0.267 with P-Values ​​of 0.083<0.05 and tstat 1.734>1.96. Thus, leadership style influences work stress, the path coefficient value of workload on work stress is 0.013 with P-Values ​​of 0.739 > 0.05 and tstat 0.334 <1.96. Thus, leadership style does not mediate the influence of workload on work stress. In conclusion, there is an influence of workload, leadership style, and stress on guidance and counseling teachers. Keywords: workload, work environment, teacher stress, leadership style. kata kunci: beban kerja, lingkungan kerja, stres guru, gaya kepemimpinan